Niechciane dziedzictwo. Piąty tom „Chłopa polskiego w Europie i Ameryce” a Chicago początku XX wieku - Luczys, Piotr (Człowiek i Społeczeństwo, 2019)
The main task of this text is to present the subject matter of the fifth volume of The Polish Peasant in Europe and America written by W.I. Thomas and F. Znaniecki. In this context, special attention will be paid to the criminal activities of Polish immigrants in Chicago in the first two decades of the 20th century. The point of departure for the reflections is the point of reference to the fragments of the five-book, repeated many times in the literature, which often do not go beyond the first three volumes, and at the same time impose a dominant and schematic interpretation discourse for the whole work. The subsequent parts of the text reconstruct the history of migratory waves coming to Chicago from the end of the 19th century on the basis of ongoing social, industrial and urban transformations, and thus the birth of urban crime. The crime history of Polish immigrants in Chicago allows us to re-examine the work of Thomas and Znaniecki from a different perspective (mainly from American sources), emphasizing at the same time the social conditions of the beginnings and the development of criminal structures in migratory environments, while at the same time drawing attention to this topic, commonly ignored in the history of Thomas and Znaniecki’s work and Polish-American relations. Piotr Luczys, Niechciane dziedzictwo. Piąty tom „Chłopa polskiego w Europie i Ameryce” a Chicago początku XX wieku [An unwanted legacy. The fifth volume of Polish Peasant in Europe and America and Chicago at the beginning of the 20th century] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVII: „Chłop polski w Europie i Ameryce” po stu latach [Polish peasant in Europe and America after one hundred years], Poznań 2019, pp. 87–116, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.